1994
DOI: 10.1302/0301-620x.76b4.8027133
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging and secondary screening for congenital dislocation of the hip

Abstract: We report the preliminary results of a continuing prospective evaluation of a screening programme for congenital dislocation of the hip (CDH) which uses ultrasound imaging to provide delayed selective screening to complement neonatal clinical screening. Of 26,952 births in the Southampton district, 1894 infants were referred for secondary screening because of a clinical abnormality or the presence of a predetermined risk category for CDH. Pavlik harness treatment was required for only 118 infants, giving a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 0 publications
1
53
0
1
Order By: Relevance
“…Although limited, available evidence supports the notion that a high proportion of families follow through with the initial referral. 29 However, we could not determine how many families adhere to ongoing follow-up.…”
Section: Improved Radiographic Appearancementioning
confidence: 99%
See 2 more Smart Citations
“…Although limited, available evidence supports the notion that a high proportion of families follow through with the initial referral. 29 However, we could not determine how many families adhere to ongoing follow-up.…”
Section: Improved Radiographic Appearancementioning
confidence: 99%
“…Primary care-based and population-based cohort studies [26][27][28][29][30][31][32][33][34][35][36] that include Ն1 of the major risk factors are summarized in Table 1. Consistently, only a minority (10 -27%) of all infants diagnosed with DDH in population-based studies have identified risk factors (with the exception of female gender), 30,32,33,35 and among those with risk factors, between 1% and 10% have DDH.…”
Section: Keymentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that many dysplastic hips improve without treatment particularly if they are stable. 1,2,8,18 It is important when comparing studies to ensure that similar groups of patients are included. This is particularly difficult when different ultrasound classifications are used, for example the Graf classification 5 or a classification based on the degree of cover of the femoral head.…”
Section: Vonmentioning
confidence: 99%
“…It can detect some dysplastic hips which are missed on clinical examination [1][2][3] and exclude significant dysplasia in some hips which are thought to be abnormal clinically. 4 There is, however, relatively little information in the published literature on the use of ultrasound to assess the outcome and compare splinted hips with those without splintage and the effectiveness of different splints.…”
mentioning
confidence: 99%